Equity valuation of The Boeing Company - Santana, António Henrique da Silva (2017)
The main purpose of this dissertation is to evaluate Boeing Co., an American based multinational corporation of the Aerospace and Defence sector, which is listed on the NYSE and is a part of the Dow Jones Industrial Average. BA is known for being the number one company in the Aerospace and Defence sector, as well as America’s biggest manufacturing exporter. In order to fulfil the proposed objective, several valuation methods were used – more properly the DCF, APV, DDM, and also the multiples EV/EBITDA, EV/EBIT and EV/Sales. Through an analysis of results obtained in these models, the most plausible estimation of the Boeing Co. stock value was reached. Then, to be assured that the values achieved were in line with the reality, they were compared with the ones given by an equity research made by Morgan Stanley and with the value present in the stock market at valuation date. The conclusion drawn from this process was that a recommendation to buy Boeing Co. stock had to be made.